Insect pest complex of radish and eco-friendly management of major insect pests in Meghalaya - Rai, Sabina; Patra, Sandip (Umiam : CPGSAS, CAU, 2023)
Radish (Raphanus sativus L.) is one of the most popular root crop vegetables grown throughout the year which belongs to the family Brassicaceae. Insect pests are the most important crop limiting factor. In Meghalaya there are numerous insect pests infesting radish, however, no proper information on the insect pests complex as well as effective control measures have been studied in this area. Therefore, the present study was conducted to study the insect pests complex of radish, population dynamics and eco-friendly management of major insect pests. The experiment was conducted at Entomology Research Field, Division of Crop Science, ICAR Research Complex for NEH Region, Umiam, Meghalaya. Radish (Var: Japani white long) was sown at five different sowing dates in a randomized block design (RBD) with four replications. A total of 17 insect species were recorded, out of which 13 species were observed as insect pests, and 4 were natural enemies. Insect pests recorded belongs to 4 orders and 7 families viz., 6 Coleoptera, 3 Lepidoptera, 3 Hemiptera and 1 Hymenoptera. Among the insect pests, striped flea beetle (Phyllotreta striolata Fab.) and crucifer flea beetle (Phyllotreta cruciferae Goeze) were found the most damaging pest and considered to be the major insect pests of radish in this region. Population dynamics showed that number of striped flea beetle ranged from 0.67 to 12.60 beetles/plant during different observations with peak population on third week of January i.e. 3rd SMW whereas population of crucifer flea beetle ranged from 0.27 to 6.47 beetles/plant with peak population on third week of January i.e. 3rd SMW. Striped flea beetle and crucifer flea beetle population were negatively significant with maximum, minimum and average temperature. The first and second sowing recorded less infestation of insect pests and highest yield 266.53q/ha and 264.60q/ha, respectively and the lowest yield was obtained from late sowing i.e. 5th sowing (230.70q/ha). Cypermethrin was found to be most effective treatment against striped flea beetle with 1.98 beetle/plant and 81.06% reduction over control and crucifer flea beetle with 1.06 beetle/plant and 78.75% reduction over control. Amongst the bio-pesticide Metarhizium robertsii, neem oil, and Beauveria bassiana was found effective in reducing beetle population over untreated control. The highest yield of radish 328q/ha (with leaves) and 231.70q/ha (without leaves) was observed in cypermethrin treated plot. The present study concludes that early sowing during rabi season i.e. mid-October to mid-November maybe sown to avoid the severity of insect pests. Cypermethrin may be used for effective management of flea beetles. Among biopesticides, Metarhizium robertsii, neem oil and Beauveria bassiana may be employed safely for organic management of these pests of radish.
Keywords: Radish -- Insect pest; Insect pests -- Management -- Meghalaya